2021
DOI: 10.1038/s41467-021-22809-6
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of three-dimensional photonic crystals

Abstract: Many butterflies, birds, beetles, and chameleons owe their spectacular colors to the microscopic patterns within their wings, feathers, or skin. When these patterns, or photonic crystals, result in the omnidirectional reflection of commensurate wavelengths of light, it is due to a complete photonic band gap (PBG). The number of natural crystal structures known to have a PBG is relatively small, and those within the even smaller subset of notoriety, including diamond and inverse opal, have proven difficult to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 40 publications
0
45
0
Order By: Relevance
“…These biological structures composed of subwavelength nanoarrays provide a certain refractive index gradient, which inhibits the reflection of light to a large extent, thereby increasing the transmittance of large-scale wavelength and incident angle. [40] The slow photon effect produced by photonic crystal structure has been proved theoretically and experimentally to be a promising solution to promote photocatalysis by prolonging the residence time of photons in materials to increase light absorption in semiconductors. [41] Inspired from biological photonic structure, photocatalysts with localized surface plasma resonance (LSPR) which induces enhanced light absorption can be obtained through the appropriate 3D microstructures.…”
Section: Bionic Nanostructural Photocatalysts With Efficient Light Ca...mentioning
confidence: 99%
“…These biological structures composed of subwavelength nanoarrays provide a certain refractive index gradient, which inhibits the reflection of light to a large extent, thereby increasing the transmittance of large-scale wavelength and incident angle. [40] The slow photon effect produced by photonic crystal structure has been proved theoretically and experimentally to be a promising solution to promote photocatalysis by prolonging the residence time of photons in materials to increase light absorption in semiconductors. [41] Inspired from biological photonic structure, photocatalysts with localized surface plasma resonance (LSPR) which induces enhanced light absorption can be obtained through the appropriate 3D microstructures.…”
Section: Bionic Nanostructural Photocatalysts With Efficient Light Ca...mentioning
confidence: 99%
“…4,[16][17][18] The diamond dielectric lattice, which possesses a wide and complete omnidirectional photonic bandgap at low refractive index contrasts, is one of the most suitable candidates to make photonic crystals. 4,[19][20][21][22] Colloids are desirable building blocks for the fabrication of photonic crystals because their size is comparable to the wavelength of visible light. 10,[23][24][25] However, the sphere packing factor of the diamond lattice is 0.34, which is significantly smaller than the packing factor of 0.74 for the facecentered cubic lattice.…”
Section: Introductionmentioning
confidence: 99%
“…The cubic diamond has a large complete photonic bandgap at low frequencies, while the hexagonal diamond has only a relatively small complete photonic band gap at high frequencies. 22 The two polymorphs, both comprising tetrahedral coordination, differ in the relative arrangements of each particle with its four nearest neighbours. 17,27 For the cubic diamond, all four nearest neighbours are connected in a staggered conformation.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we propose that the rotational information required for fabricating different kinds of crystal structures can be incorporated not only into the geometry of colloidal particles but also into the shape of the patches. Simulations have shown that patchy particles with eclipsed triangular patches crystallize, with 100% eclipsed conformation, into clathrate hydrates, which can be used as a template for fabricating photonic band gap materials . With few exceptions, colloidal patchy particles fabricated in experiments have circular patches.…”
Section: Introductionmentioning
confidence: 99%